REKOMENDASI PEMUPUKAN FOSFOR (P) PADA PERTANAMAN JAGUNG BERDASARKAN STATUS P TANAH DI KECAMATAN KINALI, LUHAK NAN DUO DI KABUPATEN PASAMAN BARAT - Yulinar Zubaidah (Jurnal Solum, 2008)
A study of P – nutrient status (P – soil) in the maize production central in Kinali, Luhak Nan Duo in Pasaman, Sub Regency Pasaman Barat to find of the recommendation of phosphorous (P) fertilization. A study is conducted from October to December 2005. Method of research by crossed land area and took soil sampling with composite. Each soil sampling represented of land area research 50 – 80 ha with 0 – 20 cm dept for land area 7702,2 ha and 97 soil sample and then analyzed by Bray II methods. From 7702,2 ha of land area were survey founded P high content 5351,5 ha (69,4 %), P – with middle content 1487,5 ha (19,3 %) and P – lower content 863,2 ha (11,2 %). Based on soil P – status, P nutrient requirement to 90,250 and 500 kg SP 36 respectively and yield prospecting 4,5 ton/ha with 14 % water content equal to 8 ton dry grain seed at harvesting with water content 25%.Key Words: P-fertilizer, Fertilization Recommendation, Soil P-status